Englands faiths defender vindicated: or, A word to clear a most foul, damnable and scandalous aspersion, which hath been cast upon that patient and suffering Prince, Charles II: By some villanous and seditious persons, that he should have renounced the Protestant religion, and Church of England, and have embraced Popery. Published out of Christian and loyal duty (Early English Books Online / EEBO, 1660)
eebo-0018